Differentiation patterns of mouse embryonic stem cells and induced pluripotent stem cells into neurons - Nakamura, Mai (Cytotechnology, 2014)
Mouse embryonic stem (ES) cells and induced pluripotent stem (iPS) cells have the ability to differentiate in vitro into various cell lineages including neurons. The differentiation of these cells into neurons has potential applications in regenerative medicine. Previously, we reported that a chick dorsal root ganglion (DRG)-conditioned medium (CM) promoted the differentiation of mouse ES and iPS cells into neurons. Here, we used real-time PCR to investigate the differentiation patterns of ES and iPS cells into neurons when DRG-CM was added. DRG-CM promoted the expression levels of βIII-tubulin gene (a marker of postmitotic neurons) in ES and iPS cells. ES cells differentiated into neurons faster than iPS cells, and the maximum peaks of gene expression involved in motor, sensory, and dopaminergic neurons were different. Rho kinase (ROCK) inhibitors could be very valuable at numerous stages in the production and use of stem cells in basic research and eventual cell-based therapies. Thus, we investigated whether the addition of a ROCK inhibitor Y-27632 and DRG-CM on the basis of the differentiation patterns promotes the neuronal differentiation of ES cells. When the ROCK inhibitor was added to the culture medium at the initial stages of cultivation, it stimulated the neuronal differentiation of ES cells more strongly than that stimulated by DRG-CM. Moreover, the combination of the ROCK inhibitor and DRG-CM promoted the neuronal differentiation of ES cells when the ROCK inhibitor was added to the culture medium at day 3. The ROCK inhibitor may be useful for promoting neuronal differentiation of ES cells.